UJI DAYA TERIMA DAN NILAI GIZI BAKSO YANG BERBAHAN DASAR TEPUNG RUMPUT LAUT - Rahmi .; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Meatballs is a preferably snack food allcircles. Meatballs had interesting a spherical shape and savory flavor. This research aims to determine the acceptability test and iodine content and crude fiber of modified meatballs with Seaweed flour and tapioca flour. This experimen designt was completely randomized design with of two factors are Seaweed flour and tapioca flour with composition of 30%:10%, 20%:20%, 10%:30%. Test acceptability meatballs modified Seaweed flour and tapioca flour 30 students people of the Faculty of public health University North Sumatera and nutrient analysis was tested in laboratory of industrial research and standarization Agency Medan and Biochemistry Faculty Mathematics and Natural Sciences.The results organoleptic test based on color, aroma, flavor, and texture meatballs showed the most preferred are meatballs mixture of seaweed flour 20% and tapioca flour 20%. The result of nutrional content analysis showed that three treatments has content ofiodine 74,03 mg/kg, 49,79 mg/kg, 26,11 mg/kg and crude fiber 9,7%, 7,4%, 3,4%.Then suggested so that citizen can be meatballs modified with seaweed flour and tapioca flour as a food alternatives because it contains iodine and crude fiber required the body.Keywords: Meatballs, Seaweed flour, Tapioca flour, Acceptability test, Nutrient composition